Floristic notes from Bessarabia No. 241-276 - Pavel Pînzaru; Victor Sfeclă; Valentina Cantemir (Acta et Commentationes: Ştiinţe Exacte şi ale Naturii)
The paper presents new growing stations for 36 species of rare vascular plants from the spontaneous flora of the Republic of Moldova, highlighted as the result of the new floristic investigations carried out from the spring to the summer of the current year. The species Valerianella eriocarpa Desv. was recorded for the first time in the local flora, the presence of 7 rare species, little known previously, was confirmed and they were proposed to be included in the List of protected species and in The Red Book of the Republic of Moldova, 4th edition: Carex pseudocyperus L., C. strigosa Huds., C. vesicaria L., Epipactis leptochila (Godfery) Godfery, Fraxinus coriariifolia Scheele, Linum catharticum L. Senecio macrophyllus M.Bieb., and for the species Klasea bulgarica (Acht. & Stoj.) Holub, indicated only for one station in Batîr commune, Cimișlia district, from where it disappeared, another station was registered in the same locality.